Evaluation and Error Correction of Satellite Rainfall Using Dense Network of Rain Gauges Over Mumbai - Neha Rajput; Amarjyothi Kasimahanthi; Venkatrami Reddy; Hashmi Fatima; Preveen Kumar Devarajan; V. S. Prasad (Journal of the Indian Society of Remote Sensing, 2026)

Evaluation of soil moisture forecasts for landslide-prone areas in the Western Himalayas: A case study - Hashmi Fatima; M. N. Raghavendra Sreevathsa; John P. George; V. S. Prasad (Theoretical and Applied Climatology, 2026)

Diosgenin-loaded niosomes ameliorate cadmium-induced neurotoxicity and endocrine disruption in female rats through modulation of oxidative stress, apoptosis, and inflammatory markers - Kanza Hashmi; Ammara Saleem; Shakila Sabir; Shahana Ehsan; Aisha Mobashar; Muhammad Imran khan; Shahnaz; Zulcaif Ahmad; Muhammad Furqan Akhtar; Musaab Dauelbait; Amir Bouallegue; Esmael M. Alyami; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Long-term trends in heavy metal contamination of marine sediments in the Arabian Gulf: A meta-analysis - S. Swetha; S. Veerasingam; S. Rajendran; Hassan Hassan; Muhammad Zia U. R. Rahman Hashmi; Hamood Alsaadi; Nelson Rangel-Buitrago; Fadhil N. Sadooni (Environmental Monitoring and Assessment, 2025)
Heavy metal (HM) contamination in marine sediments is a critical environmental concern due to its potential ecological and human health impacts. This study provides a comprehensive assessment of the spatial and temporal evolution of HM contamination in Arabian Gulf sediments over a 33-year period (1991–2024). Contamination levels were evaluated using key sediment quality indices such as the contamination factor (CF), geoaccumulation index (I g ₑₒ), pollution load index (PLI), and ecological risk index (ERI) based on available meta-data. Spatial analysis revealed that marine sediments along the Iranian and Saudi Arabian coasts exhibited higher contamination levels compared to those of other Gulf countries. This elevated contamination is likely attributed to industrial discharges, oil spills and effluent releases from desalination plants. Arsenic (As), cadmium (Cd), copper (Cu), nickel (Ni), and lead (Pb) emerged as the primary toxic contributors to sediment pollution. Overall, HM contamination status in the region is predominantly low to moderate, with localized hotspots near industrialized coastal zones. The study highlights the need for scientifically informed waste management strategies to mitigate HM contamination, particularly in nearshore environments impacted by industrial activities. Furthermore, it recommends the implementation of continuous monitoring programs to track temporal trends and identify emerging contamination sources. These findings provide critical insights for environmental managers and policymakers in developing sustainable pollution mitigation frameworks and enhancing the resilience of marine ecosystems in the Arabian Gulf.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Retraction Note: Development and evaluation of methotrexate-loaded nanoemulsion formulation for topical treatment of psoriasis - Sheikh Abdur Rashid; Faiza Naseem; Pervaiz Akhtar Shah; Hamna Batool Hashmi; Mudassar Mazher; Mohammad S. Mubarak; Javad Sharifi-Rad; Muhammad Badar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Development and evaluation of methotrexate-loaded nanoemulsion formulation for topical treatment of psoriasis - Sheikh Abdur Rashid; Faiza Naseem; Pervaiz Akhtar Shah; Hamna Batool Hashmi; Mudassar Mazher; Mohammad S. Mubarak; Javad Sharifi-Rad; Muhammad Badar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

An integrated assessment of fecal sludge management (FSM) in Islamabad, Pakistan: challenges and treatment solutions - N. Maqbool; S. J. Khan; I. Hashmi (International Journal of Environmental Science and Technology, 2025)

Charting achievements: a two-year retrospective of the society for environmental geochemistry and health (SEGH) and the evolving strategies - A. Argyraki; M. J. Watts; M. Abdou; W. Ahmad; F. F. Ajayi; T. An; M. Barbieri; J. K. Biswas; M. Gaberšek; G. Gibson; M. Z. Hashmi; O. S. Humphrey; et al. (Environmental Geochemistry and Health, 2024)

Integration of chitosan coating and short-term hypobaric treatment extends postharvest life and upregulates defense-related enzymes in apple fruit - Syed Umair Shah; Majid S. Hashmi; Muhammad Rafiullah Khan; Ayaz Ahmad; Aysha Riaz; Yosef Al Shoffe; Said Wahab; Muhammad Ayub; Antonio Ippolito (European Journal of Plant Pathology, 2024)

Combination of rosemary oil and potassium sorbate controls anthracnose in mango fruit by triggering defense-related enzymes - Haris Bilal; Majid S. Hashmi (Physiological and Molecular Plant Pathology, 2023)

Future process options for brine sludge management from the chlor-alkali industry - S. Verma; S. Suresh; M. Mili; P. Diwedi; H. Bajpai; M. A. Khan; S. A. R. Hashmi; S. K. S. Rathore; A. K. Srivastava (International Journal of Environmental Science and Technology, 2023)

Central composite rotatable design for optimization of trihalomethane extraction and detection through gas chromatography: a case study - S. Rasheed; I. Hashmi; Q. Zhou; J. K. Kim; L. C. Campos (International Journal of Environmental Science and Technology, 2023)
Central composite rotatable design (CCRD) was employed to optimize initial temperature (ºC), ramp function (ºC/min) and salt addition for trihalomethane extraction/quantification from the drinking water distribution network in Ratta Amral, Rawalpindi., Pakistan. Drinking water samples were collected from the treatment plant, overhead reservoir and consumer’s taps. The USEPA method for trihalomethane detection 551.1 via gas chromatography was applied using liquid–liquid extraction. The experiments with input variables for sample preparation and operational conditions were performed in a randomized order as per design of experiment by central composite rotatable design and responses were evaluated for model development. A significant ( p = 0.005) two-factor interaction model was optimized. Initial temperature was observed to be insignificant ( p = 0.64), while ramp function ( p = 0.0043) and salt addition ( p = 0.04) were significant. Product of salt addition and ramp was significant ( p = 0.004), while product of initial temperature and salt addition was insignificant ( p = 0.008). With a desirability function of 0.97, an initial temperature of 50 ºC, 6 ºC rise/min to 180 ºC and 0.5 g salt were optimized. It was found that development and optimization of the analytical methods for rapid trihalomethane detection would improve optimization of the current treatment practices in the country.

Spatial prediction and mapping of the COVID-19 hotspot in India using geostatistical technique - Farhana Parvin; Sk Ajim Ali; S. Najmul Islam Hashmi; Ateeque Ahmad (Spatial Information Research, 2021)

Accessibility and site suitability for healthcare services using GIS-based hybrid decision-making approach: a study in Murshidabad, India - Farhana Parvin; Sk Ajim Ali; S. Najmul Islam Hashmi; Aaisha Khatoon (Spatial Information Research, 2021)

Application of groundwater flow model in assessing aquifer layers interaction in arid catchment area - S. Al-Hashmi; L. Gunawardhana; A. Sana; M. Baawain (International Journal of Environmental Science and Technology, 2020)

Evidence for craniofacial enhancer variation underlying nonsyndromic cleft lip and palate - Vershanna E. Morris; S. Shahrukh Hashmi; Lisha Zhu; Lorena Maili; Christian Urbina; Steven Blackwell; Matthew R. Greives; Edward P. Buchanan; John B. Mulliken; Susan H. Blanton; W. Jim Zheng; Jacqueline T. Hecht; et al. (Human Genetics, 2020)

Chitosan–aloe vera gel coating delays postharvest decay of mango fruit - Sadiq Shah; Majid S. Hashmi (Horticulture, Environment, and Biotechnology, 2020)

Genetic Status and Endosymbionts Diversity of Bemisia tabaci (Gennadius) on Hosts Belonging to Family Malvaceae in India - T R Hashmi; S R Devi; A Ahmad; N M Meshram; R Prasad (Neotropical Entomology, 2019)

High-performing antifouling bacterial consortium for submerged membrane bioreactor treating synthetic wastewater - H. Waheed; S. Pervez; I. Hashmi; S. J. Khan; S.-R. Kim (International Journal of Environmental Science and Technology, 2018)

Interaction between irbesartan, peroxisome proliferator-activated receptor (PPAR-γ), and adiponectin in the regulation of blood pressure and renal function in spontaneously hypertensive rats - S. Afzal; M. A. Sattar; Edward J. Johns; Mohammed H. Abdulla; Safia Akhtar; Fayyaz Hashmi; Nor Azizan Abdullah (Journal of Physiology and Biochemistry, 2016)

Examination of CK2α and NF-κB p65 expression in human benign prostatic hyperplasia and prostate cancer tissues - Fatima Qaiser; Janeen H. Trembley; Sarah Sadiq; Iqbal Muhammad; Rubina Younis; Shoaib Naiyar Hashmi; Badar Murtaza; Thomas S. Rector; Abdul Khaliq Naveed; Khalil Ahmed (Molecular and Cellular Biochemistry, 2016)

Seismic microzonation for Muscat region, Sultanate of Oman - I. El-Hussain; A. Deif; K. Al-Jabri; A. M. E. Mohamed; G. Al-Rawas; M. N. Toksöz; N. Sundararajan; S. El-Hady; S. Al-Hashmi; K. Al-Toubi; M. Al-Saifi; Z. Al-Habsi (Natural Hazards, 2013)

Deterministic seismic hazard assessment for Sultanate of Oman - A. Deif; I. El-Hussain; K. Al-Jabri; N. Toksoz; S. El-Hady; S. Al-Hashmi; K. Al-Toubi; Y. Al-Shijbi; M. Al-Saifi (Arabian Journal of Geosciences, 2013)

Probabilistic seismic hazard maps for the sultanate of Oman - I. El-Hussain; A. Deif; K. Al-Jabri; N. Toksoz; S. El-Hady; S. Al-Hashmi; K. Al-Toubi; Y. Al-Shijbi; M. Al-Saifi; S. Kuleli (Natural Hazards, 2012)

Evaluation of short-period rainfall estimates from Kalpana-1 satellite using MET software - SOMA SEN ROY; SUBHENDU BRATA SAHA; HASHMI FATIMA; S K ROY BHOWMIK; P K KUNDU (Journal of Earth System Science, 2012)

Treatment of vegetable oil mill effluent using crab shell chitosan as adsorbent - M. Geetha Devi; Z. S. Shinoon Al-Hashmi; G. Chandra Sekhar (International Journal of Environmental Science and Technology, 2012)

Experimental validation and docking studies of flavone derivatives on aldose reductase involved in diabetic retinopathy, neuropathy, and nephropathy - Pagadala Nataraj Sekhar; P. B. Kavi Kishor; P. K. Zubaidha; A. M. Hashmi; T. A. Kadam; Lakkireddy Anandareddy; Marc De Maeyer; K. Praveen Kumar; B. Vijaya Bhaskar; T. Munichandrababu; G. Jayasree; P. V. B. S. Narayana; et al. (Medicinal Chemistry Research, 2011)

On radiative forcing of sulphate aerosol produced from ion-promoted nucleation mechanisms in an atmospheric global model - Hashmi Fatima; H. C. Upadhyaya; S. N. Tripathi; O. P. Sharma; Fangqun Yu (Meteorology and Atmospheric Physics, 2011)

PKC? inhibits the hyperglycemia-induced apoptosis signal in adult rat ventricular myocytes - Ashwani Malhotra; Barinder P. S. Kang; Sayed Hashmi; Leonard G. Meggs (Molecular and Cellular Biochemistry, 2005)